2015
DOI: 10.1111/jori.12062
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Truncated Data Samples in Operational Risk Modeling

Abstract: This article addresses challenges of estimating operational risk regulatory capital when a loss sample is truncated from below at a data collection threshold. Recent operational risk literature reports that the attempts to estimate loss distributions by the maximum likelihood method are not always successful under the truncation approach that accounts for the existence of censored losses—the likelihood surface is sometimes ascending with no global solution. The literature offers an alternative called the shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…This speeds computer runtime by almost an order of magnitude, so this approximation is used for this severity for both MLE and RCE-based capital estimates. Also derived in Appendix D is a closed-form analytic expression for the mean of 61 As mentioned previously, these findings are exactly consistent with other empirical results in the literature (for example, see Ergashev et al, 2014, andCavallo, 2012a). 62 See for example, Opdyke, 2013, Opdyke and Cavallo, 2012a, 2012b, Zhou et al, 2013, and Joris, 2013 These are three of the four parametric severity distributions listed in the most recent Interagency Guidance on Operational Risk AMA severity estimation (see OCC, 2014 the Truncated LogGamma severity, 64 which also decreases runtimes over the alternative requiring numeric integration.…”
Section: Severity (And Frequency) Distributionssupporting
confidence: 85%
See 3 more Smart Citations
“…This speeds computer runtime by almost an order of magnitude, so this approximation is used for this severity for both MLE and RCE-based capital estimates. Also derived in Appendix D is a closed-form analytic expression for the mean of 61 As mentioned previously, these findings are exactly consistent with other empirical results in the literature (for example, see Ergashev et al, 2014, andCavallo, 2012a). 62 See for example, Opdyke, 2013, Opdyke and Cavallo, 2012a, 2012b, Zhou et al, 2013, and Joris, 2013 These are three of the four parametric severity distributions listed in the most recent Interagency Guidance on Operational Risk AMA severity estimation (see OCC, 2014 the Truncated LogGamma severity, 64 which also decreases runtimes over the alternative requiring numeric integration.…”
Section: Severity (And Frequency) Distributionssupporting
confidence: 85%
“…So from an empirical perspective, we are squarely in the bias-zone: bias is material for many, if not most estimations of capital at the UoM level. 38 In fact, this is exactly what Ergashev et al (2014) found in their study comparing capital based on shifted vs. truncated lognormal severity distributions. The latter exhibited notable bias that disappeared as sample sizes increased up to n = 1,000, exactly as in the simulation study in this paper.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…This is the part of the aggregate model where initial assumptions about the data collection threshold are most influential. A number of authors have examined some aspects of this topic in the past (e.g., Cavallo et al 2012;Chernobai et al 2007;Ergashev et al 2016;Luo et al 2007;Moscadelli et al 2005). The modeling approaches they (collectively) considered include: the empirical approach, the "naive" approach, the shifted approach, and the truncated approach.…”
Section: Introductionmentioning
confidence: 99%